Penganekaragaman Bahan Pangan Sebagai Strategi Mempertahankan Daya Tahan Tubuh Di Masa Pandemi Covid-10 - Widyaningrum, Bakti; Helbawanti, Octaviana; Khoerunisa, Nisa; Srigustini, Astri (Universitas Nusantara PGRI Kediri, 2022)
Food diversification can be done to support the fulfillment of individual calorie and nutritional needs in order to carry out activities properly. The purpose of community service activities is that participants can understand the concepts of the Nutrient Adequacy Number (RDA) and Energy Adequacy Number (AKE), the preparation of food composition according to the recommendation of the Ministry of Health's